2012
DOI: 10.1152/ajpendo.00524.2011
|View full text |Cite
|
Sign up to set email alerts
|

High-glycemic index carbohydrates abrogate the antiobesity effect of fish oil in mice

Abstract: index carbohydrates abrogate the antiobesity effect of fish oil in mice. Am J Physiol Endocrinol Metab 302: E1097-E1112, 2012. First published February 14, 2012 doi:10.1152/ajpendo.00524.2011Fish oil rich in n-3 polyunsaturated fatty acids is known to attenuate diet-induced obesity and adipose tissue inflammation in rodents. Here we aimed to investigate whether different carbohydrate sources modulated the antiobesity effects of fish oil. By feeding C57BL/6J mice isocaloric high-fat diets enriched with fish oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 75 publications
5
40
0
1
Order By: Relevance
“…In agreement with previous studies in male mice (14,30,32), intake of a diet with high protein/sucrose ratio did not protect the mice against high-fat diet-induced impairment of glucose tolerance at 3 mo (Fig. 2B).…”
Section: A High Protein/sucrose Ratio Diminishes High-fat Dietinducedsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies in male mice (14,30,32), intake of a diet with high protein/sucrose ratio did not protect the mice against high-fat diet-induced impairment of glucose tolerance at 3 mo (Fig. 2B).…”
Section: A High Protein/sucrose Ratio Diminishes High-fat Dietinducedsupporting
confidence: 93%
“…However, these models cannot be used to distinguish whether the observed metabolic dysfunctions result from the obese state or from the high-fat feeding. Rodent studies have shown that obesity is prevented if the increase in dietary fat is accompanied by a high protein-to-sucrose ratio (12,14,30,32,33,36). This may reflect higher satiety and diet-induced thermogenesis when the protein content in the diet is increased (31).…”
mentioning
confidence: 99%
“…These differences impinge on the important question as to whether hyperinsulinemia is a compensatory action to counteract obesity-elicited inflammation and peripheral insulin resistance or whether increased plasma insulin precedes obesity development, inflammation, and insulin resistance. Whereas the canonical view favors the first possibility (1, 40), we and others have recently argued that a high level of insulin is a prerequisite for HF diet-induced obesity (41)(42)(43). In keeping with this view, adipose-specific insulin receptor knock-out mice are protected against diet-induced obesity (44).…”
Section: Discussionmentioning
confidence: 82%
“…Mice were killed by cervical dislocation. iBAT, iWAT, and eWAT were dissected as previously described (15). All mouse experiments were approved by the Norwegian or Danish Animal Research Authority.…”
Section: Experimental Mice and Tissue Samplingmentioning
confidence: 99%